2019
DOI: 10.1186/s12885-019-5904-x
|View full text |Cite
|
Sign up to set email alerts
|

SREBP1 promotes the invasion of colorectal cancer accompanied upregulation of MMP7 expression and NF-κB pathway activation

Abstract: Background Sterol-regulatory element binding protein 1 (SREBP1), an intracellular cholesterol sensor located in the endoplasmic reticulum, regulates the intracellular cholesterol by the Insig-Srebp-Scap pathway. Over-expression of SREBP1 can cause dyslipidemia. SREBP1 can regulate the metabolic pathway, and then promote the proliferation of tumor cells. However, there is no relevant research of metastasis and invasion in the field of colorectal cancer (CRC). Methods Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…ESCC tumor tissue analysis showed that patients in the high SREBP1 expression group had significantly poorer differentiation, more lymphatic metastasis and higher Ki-67 expression levels compared with those in the low SREBP1 expression group. The present data suggested that SREBP1-overexpression may contribute to the development of ESCC, which is consistent with SREBP1-overexpression previously described in ovarian tumor (24,48), glioblastoma (25), prostate (27), colorectal (28) and breast cancer (50,51), and nasopharyngeal carcinoma (NPC) (48). In addition, a number of studies have reported that SREBP1 participates in the proliferation of multiple cancer types (24,26,35,49).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ESCC tumor tissue analysis showed that patients in the high SREBP1 expression group had significantly poorer differentiation, more lymphatic metastasis and higher Ki-67 expression levels compared with those in the low SREBP1 expression group. The present data suggested that SREBP1-overexpression may contribute to the development of ESCC, which is consistent with SREBP1-overexpression previously described in ovarian tumor (24,48), glioblastoma (25), prostate (27), colorectal (28) and breast cancer (50,51), and nasopharyngeal carcinoma (NPC) (48). In addition, a number of studies have reported that SREBP1 participates in the proliferation of multiple cancer types (24,26,35,49).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, according to the significant relationship between SREBP1 expression levels and lymphatic metastasis shown in the present study, SREBP1 was identified as a promoting factor regulating VEGF-C formation and secretion. Recently, studies have suggested that SREBP1 can participate in the metastasis of multiple tumors (28,49,51). Wound healing and Transwell assays in the present study revealed that cell migration and invasion were either upregulated or downregulated in response to SREBP1-overexpression or knockdown in ESCC cells, respectively.…”
Section: Discussionsupporting
confidence: 49%
“…We showed that the expression of SREBP1 was associated with the tumorigenic properties where it was associated with the EMT makers. Our results were supported by previous studies where increased SREBP1 expression facilitated EMT in breast and colon cancer [26,35]. In addition, studies have reported that SREBP1 is involved in the proliferation of multiple cancers [22,24,34,37].…”
Section: Discussionsupporting
confidence: 92%
“…SREBP1 is a critical transcription factor that controls the expression of genes important for the uptake and synthesis of lipids, such as cholesterol, fatty acids, and phospholipids [32]. Accumulating evidence suggests that SREBP1 facilitates tumor progression, and the upregulation of SREBP1 has often been detected in many cancer types [22][23][24][25][26][27][33][34][35][36]. In this study, we first identified an increased SREBP1 expression in different ESCC cohorts, which was in an inverse relationship with tumor suppressor miR-142-5p.…”
Section: Discussionmentioning
confidence: 76%
“…The MMPs, in addition to digesting the ECM was also reported to have additional cellular functions; thus, they appear to be critical regulators of specific cell signal pathways. 29,41,42 MMPs majorly implicated in tissue remodeling, 1 understand the cross-talk if any between MMP7 and Hsp90. We reported earlier that cancer cells that exhibit resistance to Hsp90 inhibition might become aggressive when challenged with Hsp90 inhibitors.…”
Section: Discussionmentioning
confidence: 99%